Retrospective Investigator-Initiated Trial on Tocopherol Acetate Vaginal Administration in Pre-and Postmenopausal Women - Noemi Venditti; Giulio Petronio Petronio; Antonio Guarnieri; Laura Pietrangelo; Angela Spicciato; Alessio Colalillo; Giovanna Paola Sabusco; Dionisio Franco Barattini; Aldo Di Franco; Stefano Papini; Francesco Cosentino; Roberto Di Marco (Diseases, 2024)
Background: Menopause, a natural phase in a woman’s life, often adversely affects physical, mental, sexual, and emotional well-being due to low estrogen levels. This study examines the impact of vaginal ovules with tocopherol acetate (Filme Gyno-V® ovules, manufactured by Panin Srl and distributed by Hulka Srl, Italy), 500 mg per ovule, on vaginal health in pre- and menopausal women. Methods: Fifty women aged 50–70 were divided into menopausal (28) and premenopausal (22) cohorts and treated with the ovules for two weeks, with assessments before and after treatment. Results: The findings showed that distressing symptoms of vaginal atrophy, such as dryness, itching, and pain during intercourse, were resolved post-treatment. A molecular analysis revealed a reduction in Escherichia coli in both cohorts and an increase in three species of Lactobacillus in premenopausal patients. Conclusions: This study concludes that Filme Gyno-V ovules may benefit vaginal health by alleviating atrophy symptoms and promoting healthy vaginal microbiota.